Group of young adults dressed in traditional Icelandic costumes (North Dakota State University Libraries, Institute for Regional Studies;)
Large group of young adults dressed in Icelandic costumes. Gelatin silver prints; 30 x 24 cm. Title supplied by staff. Photographer unknown.